Mujeres, acciones afirmativas y capacidades humanas - Luz Mireya Mendieta Pineda; Wilmar Niño Hernández; Edson Romario Pérez Martínez (Eleuthera)
This article seeks to determine argumentative elements within the discussions of feminist studies. Mainly, regarding the scope of affirmative actions, the theory of human capabilities and the internationalist feminism of Martha Nussbaum. The research suggests that the theory proposed by the american philosopher allows for a clearer response to the structural problem of inequality and discrimination that women have in the public sphere. It is determined that the dynamics regarding affirmative actions to achieve equality are observed without a gradual scope in the formal and material sphere, under the dynamics of the constant presence of violence and exclusion in gender issues.